2005
DOI: 10.5713/ajas.2005.22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pelleted Sugarcane Tops on Voluntary Feed Intake, Digestibility and Rumen Fermentation in Beef Cattle

Abstract: Four male crossbred beef steers about 2 years old were used in a 4×4 Latin square design to investigate the effect of pelleted sugarcane tops on voluntary feed intake, rumen fermentation and digestibility of nutrients. Experimental treatments were; Control (dried-chopped sugarcane tops (DCST)); PS1 (Pelleted sugarcane tops at 1 cm of diameter); PS2 (Pelleted sugarcane tops at 2 cm of diameter) and PS3 (Pelleted sugarcane tops at 3 cm of diameter). Roughage intake and total dry matter intake were 1.59, 1.62, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The animals were offered 10 kg green, ad-lib dry grass and 2.5 kg of concentrate mixture daily. Approximately 500 ml of rumen fluid was collected via a stomach tube located in the mid part of the rumen and connected to a vacuum pump at 0,2,4,6hrs post feeding (52, 19). About 100 ml rumen fluid was passed through four layers of cheese cloth to remove particulate matter.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were offered 10 kg green, ad-lib dry grass and 2.5 kg of concentrate mixture daily. Approximately 500 ml of rumen fluid was collected via a stomach tube located in the mid part of the rumen and connected to a vacuum pump at 0,2,4,6hrs post feeding (52, 19). About 100 ml rumen fluid was passed through four layers of cheese cloth to remove particulate matter.…”
Section: Methodsmentioning
confidence: 99%
“…Rumen liquor was collected on day 25 immediately before morning feeding. Approximately 500 ml of liquor was collected via a stomach tube located in the mid part of the rumen and connected to a vacuum pump (Yuangklang et al, 2005;Khampa et al, 2006a). The first 100 ml collected were discarded and the remaining liquor was passed through four layers of cheese cloth to remove particulate matter.…”
Section: Animals Diet and Collection Of Rumen Liquormentioning
confidence: 99%
“…The increasing of digesta rate of passage decreased the retention time of digesta in the digestive tract, so that its digestibility decreased (Van Soest, 1994). Those fenomenon also reported by Yuangklang et al (2005) in beef cattle which showed that IVoDMD of chopped sugar cane top was 68.80% whereas pelleted sugar cane top was 63.37%.…”
Section: Dry Matter and Organic Matter Digestibilitymentioning
confidence: 54%